Correction: Solution-processed Cu2XSnS4 (X = Fe, Co, Ni) photo-electrochemical and thin film solar cells on vertically grown ZnO nanorod arrays. Issue 54 (3rd September 2018) - Ghosh, Anima; Chaudhary, Dhirendra K.; Biswas, Amrita; Thangavel, Rajalingam; Udayabhanu, G.
Abstract : Correction for 'Solution-processed Cu2 XSnS4 (X = Fe, Co, Ni) photo-electrochemical and thin film solar cells on vertically grown ZnO nanorod arrays' by Anima Ghosh et al., RSC Adv., 2016, 6, 115204–115212.